Peran Pembelajaran Pendidikan Pancasila dan Kewarganegaraan Dalam Menangkal Bullying di Sekolah - Wismanjaya, Herdi; Robian, Abi; Handayani, Dini (Fakultas Keguruan dan Ilmu Pendidikan Universitas Pamulang, 2025)
Partner refers to SMK Sasmita Jaya 2, a vocational high school located in Pamulang District, South Tangerang City. As stated in Article 3 of Law No. 20 of 2023 of the Republic of Indonesia, education should aim to develop students' potential so they become individuals who are faithful and devoted to God Almighty, possess noble character, good health, knowledge, competence, creativity, independence, and discipline, and uphold Pancasila values as responsible citizens. Based on observations and school data, bullying cases are still frequently found at SMK Sasmita Jaya 2. One common form of bullying is social exclusion, where a student is deliberately avoided or isolated by their peers. This practice makes the excluded student feel sad, pressured, uncomfortable, and even inferior. Bullying is a serious concern for all parties, including school management, teachers, and non-educational institutions, considering the severe negative psychological impact on students. The goal of this community service program (PKM) is to provide counseling to students to raise awareness about the dangers of bullying, its negative psychological effects, and preventive measures through Pancasila and Civic Education (PPKn). This community service initiative is conducted through direct counseling sessions using several methods, including the lecture method, interactive discussion, and simulation techniques, tailored to the theme and audience. By teaching Pancasila values, such as just and civilized humanity and Indonesian unity, students are encouraged to understand the importance of respecting differences, upholding human dignity, and fostering cooperation in diversity. Through this approach, students can develop a mutual respect attitude and strengthen harmonious relationships in their daily lives. Consistent reinforcement of Pancasila and Civic Education is essential in building a school culture free from bullying, ensuring that every student feels valued and protected.